Implications of climate change on freshwater ecosystems and their biodiversity - Divya Nimma; Okram Ricky Devi; Bibek Laishram; Janjhyam Venkata Naga Ramesh; Santhosh Boddupalli; Rajaram Ayyasamy; Vineet Tirth; Amir Arabil (Desalination and Water Treatment, 2025)
Global warming is a phenomenon whereby the planet's exposure to the sun's radiation worsens from the high emission of gasses believed to trap heat within the atmosphere. Carbon dioxide (CO2) is the leading greenhouse gas majorly responsible for global warming and other related issues and is a danger to global society. This one has a particular role in portraying the key importance of the shifting climate that invariably influences water supply and agricultural production. Global warming presents complex challenges to aquatic organisms and stocks and other natural aquatic life resources. This study examines how freshwater and marine species are affected by climate change in aquatic habitats. Aquatic species' metabolism, growth, reproduction, and dispersal are all impacted by rising temperatures and altered water chemistry brought on by increased greenhouse gas emissions, especially CO2. The goal is to pinpoint the ecosystems and vulnerable species that are most impacted by these changes and suggest flexible management techniques. The suggested remedies center on creating sustainable conservation strategies that lessen the effects of climate change on aquatic biodiversity and increase these ecosystems' resilience. The socio-economic interdependencies between water and climate change impact agricultural and water resources, and the pressures exerted on water bodies and water supply landscapes. Another area is related to alterations in the physical and chemical properties of the water, such as the temperature, which is a well-known effect of climate change: 'This causes abnormalities in the metabolism and physiology of aquatic species.' These alterations flow through the chain and regime of growth, reproduction, feeding habits and distribution, migration, and mass of fish and other creatures in the water system. However, the long-term effect of climate variation and climate change on freshwater ecosystems requires much scientific investigation to address challenges in aquatic ecosystem conservation and sustainability. This being the case, adaptive management solutions that address the interrelated impacts of climate change have to be applied and implemented to reduce vulnerability in aquatic ecosystems worldwide.